An End‐on‐Coordinated As4 Tetrahedron1. Issue 29 (10th June 2013) - Schwarzmaier, Christoph; Timoshkin, Alexey Y.; Scheer, Manfred
<x xml:space="preserve">Abstract</x> One time only: The reaction of [Cp*Ru(dppe)Cl] with the potent As4 transfer reagent [Ag(η2‐As4)2]+[pftb]− leads to [Cp*Ru(dppe)(η1‐As4)]+[pftb]− with an unprecedented end‐on‐coordinated As4 tetrahedron. Reaction with a second cationic ruthenium complex fragment does not lead to a second end‐on coordination but to the cleavage of one basal AsAs bond. This behavior, which differs from its phosphorus analogues, is rationalized by DFT calculations.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>